2014
DOI: 10.1111/jawr.12226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pre‐ and Post‐Fire Peak Discharge Predictions across Western U.S. Watersheds

Abstract: This study reviews five models commonly used in post-fire hydrologic assessments: the Rowe Countryman and Storey (RCS), United States Geological Survey (USGS) Linear Regression Equations, USDA Windows Technical Release 55 (USDA TR-55), Wildcat5, and U.S. Army Corps of Engineers (USACE) Hydrologic Modeling System (HEC-HMS). The models are applied to eight diverse basins in the western United States (U.S.) (Arizona, California, Colorado, Montana, and Washington) affected by wildfires and assessed by input parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Significant advances in post‐fire hydrology since the development of Rowe et al (1949) should be incorporated to improve the accuracy of predictions (Kinoshita et al, 2014). For example, sediment bulking is implicit in RCS, yet independent variables that are strongly linked to sediment production or sediment yield are not used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant advances in post‐fire hydrology since the development of Rowe et al (1949) should be incorporated to improve the accuracy of predictions (Kinoshita et al, 2014). For example, sediment bulking is implicit in RCS, yet independent variables that are strongly linked to sediment production or sediment yield are not used.…”
Section: Discussionmentioning
confidence: 99%
“…The 2‐ and 10‐year recurrence interval predictions to assess watersheds are typically used by WERT and BAER teams because there is more confidence in flood flow prediction methods at smaller recurrence intervals compared to larger intervals such as 25‐, 50‐ 100‐year (Kinoshita et al, 2014). Additionally, the recovery period for local vegetation in southern California is typically 2–7 years, which influences the hydrologic response (Bell et al, 2009; Keeley & Keeley, 1981; Kinoshita & Hogue, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models were applied to eight diverse basins in the western United States affected by wildfires. According to Kinoshita et al (2014), no one model performed sufficiently well for application to all study sites. The review results showed inconsistency between model predictions for events across the sites and poor results with larger return periods (25-and 50year events) and when applied to post-fire watershed simulations.…”
Section: Simulation Of Subsurface Flowmentioning
confidence: 97%
“…The soil burn severity map was an input for WEPP and GeoWEPP simulations to help to quantify burn effects on soils runoff and erosion. Kinoshita et al (2014) reviewed five models for post-fire peak discharge predictions: the Rowe Countryman and Storey (RCS) (Rowe et al, 1949), United States Geological Survey (USGS) Linear Regression Equations (Foltz et al, 2009), USDA Windows Technical Release 55 (TR_55) (USDA, 2009), Wildcat5 (Hawkins and Munoz, 2011), and U.S. Army Corps of Engineers (USACE) Hydrologic Modeling System et al, 2000;Letey, 2001). Post-wildfire infiltration into the unsaturated zone is controlled by fire-induced changes in soil-water storage and soil hydraulic properties.…”
Section: Introductionmentioning
confidence: 99%